Studi Deposit Monasit dan Zirkon Dalam Batuan Kuarter di Daerah Cerucuk Belitung - Soetopo, Bambang; Subiantoro, Lilik; Sularto, Priyo; Haryanto, Dwi (EKSPLORIUM, 2012)
Geologically the study area lies in the distribution of granite in a single lane of Malaysian tin, Bangka-Billiton, Karimata which is containing monazite mineral monazite.Monazite is one of the radioactive minerals containing uranium (U), thorium (Th), rare earth element (REE) in phosphate bonds. Heavy minerals sample that containing monazite 2.719% has radioactivity value until 3000 c/s. Petrographic analysis of granitic rocks contain minerals monazite 1-2% with radioactivity 200-400 c/s. Based on these considerations, it is necessary to for further research in the development and assessment of prospects for mineral monazite. The Objectives to be achieved isobjective to be achieved is to localize the prospect area distribution of monazite and zircon in the area of ​​100 km2. The results of field studies showed that the presence of monazite contained in the sand, clay as alluvial deposits derived granitic rocks. Indications are reflected in the results of radioactivity measurements of soil / alluvial ranged between 50-375 c/s, measurement of radioactivity of heavy minerals (MB) ranged between 50-150 c/s at some point discovered the location of high radioactivity values ​​ ranged between 250-1000 c/s with background value of 25-150 c/s and dan contains Th (100 – 6.545 ppm) serta contains U (15 – 639,4 ppm). The results show that in the study area indicates that the potential for monazite and zircon area ​​31,680,000 m2.